Surgical residency training in the mission setting: current status and future directions - James D Smith; Dan Poenaru; David Thompson; J Dwight Phillips (Health for All Nations, 2016)
Surgery has traditionally been an important aspect of services offered by mission hospitals, but only in the last 20 years has surgical residency training been incorporated into the mission hospital setting. A working group of surgical educators met in conjunction with the Global Missions Health Conference in November 2015 and discussed the current status of surgical training in the mission setting. This paper outlines the current status and makes recommendations for mission groups who are contemplating starting a residency training program. Potential difficulties and the importance of regional recognition of the program are discussed. The work group felt that it was important to include a strong spiritual emphasis as part of the training. Future directions and the concern about employment opportunities are explored.